Peran Manajemen Waktu dan Dukungan Keluarga dalam Membentuk Work-Life Balance Mahasiswa Part-Time Universitas Mulawarman - Zahrahtul Sa'diyah; Adelia Risma; Dea Khair Akhyari; Putri Lianna Claresta; Glacia Rosariana Eden; Rohana Nur Aini; Lusiana Desy Airswati (Indo Publishing, 2026)
The phenomenon of students working while pursuing higher education is becoming increasingly common and requires the ability to maintain a work-life balance. This study aims to analyze the role of time management and family support in shaping the work-life balance of part-time students at Mulawarman University. A descriptive qualitative approach was employed through semi-structured interviews with eight students who worked while studying. Data were analyzed using NVivo 15 through word cloud, cluster analysis, and tree map visualizations, followed by thematic analysis based on the six-phase framework of Braun and Clarke (2022). The findings indicate that time management and family support are closely related in fostering students’ work-life balance. Time management serves as a key internal factor influencing students’ ability to manage dual responsibilities, while family support functions as an external factor that strengthens psychological well-being. Students with structured time management tend to achieve a better balance between academic and work demands. Furthermore, emotional, informational, and instrumental family support enhances motivation and resilience in coping with various pressures. The study also reveals that work-life balance is dynamic and depends on individuals’ ability to adapt to changing demands.